Dual-energy computed tomography to detect early pulmonary vascular changes in children with sickle cell disease: a pilot study - Joye, Raphael; Wacker, Julie; Nguyen, Duy-Anh; Hachulla, Anne-Lise; Maggio, Albane B. R.; Cimasoni, Laurent; Lador, Frederic; Ansari, Marc; Beghetti, Maurice (Frontiers in Pediatrics, 2023)
Introduction Pulmonary hypertension (PH) is a rare and devastating complication of sickle cell disease (SCD) that might be reversible if treated early. Dual-energy computed tomography (DECT) is becoming a valuable tool for diagnosis of PH. We sought to determine if DECT can detect early signs of PH in children with SCD. Method This is a prospective observational pilot study conducted at the Geneva University Hospital. The study was approved by the local human ethic committee (CCER 2019-01975) and written informed consent was provided by all the patients and/or legal guardian. Eight children (five girls), with homozygous SCD were included and underwent full cardiology work-up with transthoracic echocardiography (TTE) and cardiopulmonary exercise test (CPET), as well as DECT. Results Median age was 11-year-old (range 8 – 12). TTE showed a normal biventricular systo-diastolic function in all. Median TRV value was 2.24 m/sec (range 1.96 – 2.98). Four children were found to have signs of vasculopathy on DECT. Of them, two had abnormal screening test. Both had increased VE/VCO2 slope during CPET and an increased tricuspid regurgitant jet velocity > 2.5 m/s on TTE. Conclusion DECT seems to be able to identify early signs of pulmonary vascular disease in children with SCD. Further studies are needed to better understand the correlation between DECT abnormalities and pulmonary circulation hemodynamic.